Potential of Heterorhabditis zealandica (Rhabditida: Heterorhabditidae) for the control of codling moth, Cydia pomonella (Lepidoptera: Tortricidae) in semi-field trials under South African conditions. Issue 2 (3rd April 2018) - de Waal, Jeanne Y.; Addison, Matthew F.; Malan, Antoinette P.
ABSTRACT: Infection of codling moth, Cydia pomonella (L.), larvae by the entomopathogenic nematode, Heterorhabditis zealandica, was studied under semi-field conditions. Late-instar diapausing codling moth larvae, coccooned in perforated cardboard strips, were used in all trials to evaluate the nematode treatments involved. A morning application of 0.5, 1.0 and 1.5 MM infective juveniles (IJs) per tree resulted in 85%, 95% and 100% codling moth larval infection, respectively. Contrasting results were obtained for an evening application, with low levels of codling moth infection (<50%). Nematode treatment strips placed in direct sunlight resulted in almost no infection (<10%), opposed to strips attaining 67% infection placed in the shade.